2011
DOI: 10.4028/www.scientific.net/amr.254.74
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Piezoelectric Properties of AlN Using MEMS Resonators

Abstract: This paper presents an effective evaluation of piezoelectric coefficients (d31 and d33) and other mechanical properties of AlN thin films using resonator structures fabricated on a single wafer. The extracted value for d31 is 1.60pm/V and the d33 value is 3.15pm/V, which are comparable to the coefficient values published in literature. Fabrication of these resonator structures is straightforward and can be incorporated with other more complex steps. Hence, these resonators can serve as an excellent test struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Complementary metal-oxide-semiconductor (CMOS) compatibility, high temperature and long term stability as well as low dielectric constants are beneficial properties of AlN. For the piezoelectric constants d 33 and d 31 values up to 6.5 pm/V and −2.9 pm/V are reported for pure AlN thin films prepared by reactive magnetron sputtering [8–10] . A significant enhancement was achieved via incorporation of scandium (Sc) into AlN, up to 27.6 pm/V for Sc x Al 1− x N thin films with x = 42.5% [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…Complementary metal-oxide-semiconductor (CMOS) compatibility, high temperature and long term stability as well as low dielectric constants are beneficial properties of AlN. For the piezoelectric constants d 33 and d 31 values up to 6.5 pm/V and −2.9 pm/V are reported for pure AlN thin films prepared by reactive magnetron sputtering [8–10] . A significant enhancement was achieved via incorporation of scandium (Sc) into AlN, up to 27.6 pm/V for Sc x Al 1− x N thin films with x = 42.5% [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…This feature enables the growth of high-quality piezoelectric films directly onto soft substrates . Recently, AlN films have been doped with scandium (Sc) atoms to improve the (out-of-plane) piezoelectric coefficient ( d 33 ) of pure AlN, which is typically around 5 pm/V . Indeed, Akiyama et al .…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, AlN films have been doped with scandium (Sc) atoms to improve the (out-of-plane) piezoelectric coefficient (d 33 ) of pure AlN, which is typically around 5 pm/V. 11 Indeed, Akiyama et al reported on AlN films doped with 43% Sc, showing an increase of d 33 by over 400%, if compared with the pure AlN film coefficient. 12 These findings were investigated by Tasnadi et al by means of an ab initio simulation, reporting that the increase of the d 33 values of the Sc-doped AlN films is attributed to an increase of the volume of the crystal cell.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally observed was an increase of the piezoelectric stress constant d 33 from up to 6.5 pC/N at x ¼ 0 (Refs. [10][11][12] to up to 27.6 pC/N for x ¼ 0.43. 13,14 Ab initio calculations in comparison with experimental data revealed the effects to be intrinsic consequences of Sc substitution on aluminium (Al) sites.…”
Section: Introductionmentioning
confidence: 99%